2016
DOI: 10.1002/chem.201601136
|View full text |Cite
|
Sign up to set email alerts
|

An Easy Access to Organic Salt‐Based Stimuli‐Responsive and Multifunctional Supramolecular Hydrogels

Abstract: By exploiting orthogonal hydrogen bonding involving supramolecular synthons and hydrophobic/hydrophilic interactions, a new series of simple organic salt based hydrogelators derived from pyrene butyric acid and its β-alanine amide derivative, and various primary amines has been achieved. The hydrogels were characterised by microscopy, table-top rheology and dynamic rheology. FTIR, variable-temperature (1) H NMR and emission spectroscopy established the role of various supramolecular interactions such as hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Compared with polymer gels, LMWGs have considerable mechanical properties; meanwhile, reversible non-covalent bonds and the functional groups of gelators confer to the gels more stimulus responsiveness (pH, light, magnetism, enzyme, ion, etc.) and better biodegradability [15,16]. Researchers have attempted to systematically modify and optimize existing gelators or to introduce diverse functional groups to form new compounds and construct progressive LMWGs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with polymer gels, LMWGs have considerable mechanical properties; meanwhile, reversible non-covalent bonds and the functional groups of gelators confer to the gels more stimulus responsiveness (pH, light, magnetism, enzyme, ion, etc.) and better biodegradability [15,16]. Researchers have attempted to systematically modify and optimize existing gelators or to introduce diverse functional groups to form new compounds and construct progressive LMWGs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of synthesis of gelator molecules, salt formation deserves special mention; it is the least time consuming high throughput, high yield process in comparison to typical covalent synthesis thereby providing means to generate a large library of potential LMWGs within a relatively short period of time. We demonstrated that such supramolecular approach was indeed useful in generating SGs for various applications such as synthesizing nanoparticles, sensing, dye adsorption, drug delivery via self‐delivery fashion etc.…”
Section: Introductionmentioning
confidence: 99%
“…“The peasant who wants to harvest in his lifetime cannot wait for the ab initio theory of weather”—in keeping with the philosophy of Hans Georg von Schnering, the author’s group has been actively involved in designing supramolecular gelators following the crystal engineering approach and successfully developed many supramolecular gels that have displayed intriguing material properties, as applicable in containing oil spills [19], synthesizing metal nanoparticles [24], sensing hazardous gas [25] and dissolved glucose, and in the adsorption of dyes [25].…”
Section: Supramolecular Gels For Various Applicationsmentioning
confidence: 99%